Data Centric Security Approach For Cloud Computing - Lakshmi Devi, Thade; Mohan Rao, S. Krishna (International Journal of Computer Sciences and Engineering, 2021)
The Data Centric Security (DCS) approach is talked about in detail. This approach is the central one utilized as a part of this postulation for upgrading cloud computing security and privacy. The Paper begins with looking into and ordering conceivable security solutions, in light of the DCS ideas in the cloud computing model. 3, at that point expands on these, to shape the applied structure for DCS implementations proposed in this exploration. [6] The normal advantages of applying the DCS way to deal with the cloud computing environments are talked about in. The extent of the application of the DCS way to deal with the cloud computing model for this proposal is recognized in the fundamental security necessities of applying the DCS way to deal with this extension are additionally cleared up. In addition, the accessible innovations that can be utilized to accomplish these necessities are looked into in that section. In light of such audits, appropriateness of these advancements is evaluated to determine a novel solution, which is among the fundamental contributions of this examination. Finally, the outline of this part is quickly introduced.